Concept and Determinants of Quality in Higher Education. A Survey Conducted amongst Spanish University Lecturers. - Cardona Rodríguez, Antonio; Barrenetxea Ayesta, Miren; Mijangos del Campo, Juan José; Olaskoaga Larrauri, Jon (Education Policy Analysis Archives, 2009)
This article presents a portion of the results obtained through a survey and about different aspects related to quality in higher education conducted with University lecturers in Spain specialized in the areas of Economics and Business during the period February-April 2008. After providing a brief description of the main features of our research this article examines the ideas about quality in higher education as well as who are the agents involved in it. This article includes a brief analysis of some of the most relevant results about the impact of actions aimed at the improvement of quality of higher education, and it analyses the opinions about different ways to understand quality.